2020
DOI: 10.1001/jamanetworkopen.2019.19607
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Characteristics With Variation in Emergency Physician Preferences for Patients

Abstract: IMPORTANCE Much of the wide variation in health care has been associated with practice variation among physicians. Physicians choosing to see patients with more (or fewer) care needs could also produce variations in care observed across physicians. OBJECTIVE To quantify emergency physician preferences by measuring nonrandom variations in patients they choose to see. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study used a large, detailed clinical data set from an electronic health record system of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Our prior investigation found that patients seen at the end of the shift are younger with fewer comorbidities, lower acuity, and more differentiated chief complaints than those seen at the start of the shift. 18 Our result that LOS is shorter at the end of shift, together with this previous finding, suggests that LOS could be measurably shaped by strategic patient selection. These findings indicate that LOS may be an unreliable metric for comparing emergency physician performance within a practice.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our prior investigation found that patients seen at the end of the shift are younger with fewer comorbidities, lower acuity, and more differentiated chief complaints than those seen at the start of the shift. 18 Our result that LOS is shorter at the end of shift, together with this previous finding, suggests that LOS could be measurably shaped by strategic patient selection. These findings indicate that LOS may be an unreliable metric for comparing emergency physician performance within a practice.…”
Section: Discussionsupporting
confidence: 74%
“…Our finding that there is variation in patient characteristics that cannot be modified by physicians across LOS quartiles demonstrates that LOS is associated with the types of patients seen, in addition to differences in physician practice patterns. Our prior investigation found that patients seen at the end of the shift are younger with fewer comorbidities, lower acuity, and more differentiated chief complaints than those seen at the start of the shift 18 . Our result that LOS is shorter at the end of shift, together with this previous finding, suggests that LOS could be measurably shaped by strategic patient selection.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Thus, observed patient characteristics vary minimally across ED physicians within the same hospital on average, although this balance may not hold in all EDs or within an ED shift. 18 In this study, we used this natural randomness to isolate physician-level variation in admission rates that was unrelated to variation in patient factors and thus mostly reflective of physician decision-making. 17 …”
Section: Methodsmentioning
confidence: 99%